Collaborative processes for exploring rural futures: The Exploring Futures Platform. Issue 1 (2nd January 2017) - Bewsell, Denise; Mackay, Alec; Kaye-Blake, William; Dynes, Robyn; Montes de Oca Munguia, Oscar; Brown, Margaret
Abstract : Collaborative approaches are becoming more common to help agriculture and rural communities navigate the range of complex issues they face. This article outlines the Exploring Futures Platform (EFP) process and critiques two case studies. EFP was developed for pastoral agriculture communities to help participants jointly define challenges and explore joint management of solutions for the future. EFP was designed to ensure successful integration of systems thinking and is built on transformational engagement, inclusion of diverse of views, delivery of real-time local data, building a system understanding, future focus, reflection and action. Lessons from the case studies using the EFP were to consider how researchers shape the discussion, make participants' and researchers' roles clear, ensure expectations of data and analysis presented are managed highlight the value of detailed case-studies identify the mandate for action from participants, build upon local knowledge, linking into local networks, and ensure continued future focus.